2014
DOI: 10.1002/ett.2803
|View full text |Cite
|
Sign up to set email alerts
|

Energy and throughput efficient cooperative spectrum sensing in cognitive radio sensor networks

Abstract: The sensing-throughput trade-off and the sensing-energy trade-off for cooperative spectrum sensing have been the subject of recent research. Two important, but often conflicting, design objectives for low-power devices are throughput and energy efficiency. These have not been comprehensively investigated jointly in cognitive radio networks for the design of spectrum sensing algorithms. This paper examines the energy-throughput trade-off for cooperative spectrum sensing and formulates an optimisation problem fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 25 publications
0
40
0
1
Order By: Relevance
“…1. Energy-efficient solutions for IoT-enabled smart cities include a wide range of topics such as lightweight protocols, scheduling optimization, predictive models for energy consumption, a cloud-based approach, low-power transceivers, and a cognitive management framework [3][4][5]. Energy harvesting allows IoT devices to harvest energy from ambient sources and/or dedicated RF sources.…”
Section: Introductionmentioning
confidence: 99%
“…1. Energy-efficient solutions for IoT-enabled smart cities include a wide range of topics such as lightweight protocols, scheduling optimization, predictive models for energy consumption, a cloud-based approach, low-power transceivers, and a cognitive management framework [3][4][5]. Energy harvesting allows IoT devices to harvest energy from ambient sources and/or dedicated RF sources.…”
Section: Introductionmentioning
confidence: 99%
“…In [21], considering the energy consumption problems of each sensing node in cooperative CR sensor network, a user selection scheme was proposed to minimize the energy consumed on each CR node based on the binary knapsack problem and its dynamic solution. After that, Ejaz et al [22] indicated that an optimal sensing, reporting, and transmission duration can be found while providing a given throughput and reliability constraint. The solution can obtain the best trade-off between energy consumption and throughput for SUs.…”
Section: Related Workmentioning
confidence: 99%
“…A statistical entropybased methodology is proposed from an information theory perspective to measure the degree of predictability in realworld radio spectrum state dynamics [14]. However, CR devices need to consume more energy to perform exclusive functionalities such as sensing and sharing [15]. Thus, it is more important to apply wireless energy harvesting method in addition to spectrum sharing to improve both energy and spectrum efficiency.…”
Section: Introductionmentioning
confidence: 99%